2020
DOI: 10.1007/s13312-020-1996-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Flexible Bronchoscopy in Ventilator-Dependent Neonates

Abstract: Objective To assess the usefulness and safety of flexible bronchoscopy in ventilated neonates with extubation failure. Method This was a prospective observational study. Flexible bronchoscopy was done in eligible patients with failure of extubation form invasive ventilation. The main outcome measure was to find the presence of any anatomic or dynamic abnormalities of the airways of these patients and the organism profile of bronchoalveolar lavage (BAL) fluid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
2
6
0
1
Order By: Relevance
“…21 Previous studies reported abnormal FB findings in 69%-80% of the patients in pediatric ICU 7,17,18 which was even higher in neonatal ICU patients (79%-98%), compared to adult patients in ICU (44%). [22][23][24] In our study, abnormal findings, were found in 91% of the patients. A high proportion of neonatal ICU patients (25%) may explain the high rate of abnormal findings in our study.…”
Section: Discussionsupporting
confidence: 56%
“…21 Previous studies reported abnormal FB findings in 69%-80% of the patients in pediatric ICU 7,17,18 which was even higher in neonatal ICU patients (79%-98%), compared to adult patients in ICU (44%). [22][23][24] In our study, abnormal findings, were found in 91% of the patients. A high proportion of neonatal ICU patients (25%) may explain the high rate of abnormal findings in our study.…”
Section: Discussionsupporting
confidence: 56%
“…[7] However, extubation failure continues to be a problem in newborns and requires evaluation of the airways. [6,8] In our study, extubation failure that occurred in half of the patients was the most common indication. Extubation could be performed without tracheostomy in 30% of these patients with treatments given according to FB and BAL results.…”
Section: Discussionmentioning
confidence: 63%
“…Our results are consistent with the results of previously published studies conducted among NICU patients reporting a 48-52% incidence of airway malacia. [6,13,18] Nosocomial pneumonia in pediatric and NICUs is associated with prolonged hospitalization, high mortality, and high health-care costs. Furthermore, pneumonia is the most common empirical antibiotic indication in the PICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexible bronchoscopy (FB) has become a progressively popular diagnostic method for airway evaluation in children[ 1 , 2 ]. Also, when mask ventilation or tracheobronchial intubation (TI) is expected to be challenging, FB is advantageous in airway safety when it is used to guide TI[ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%